Emerging and Evolving Technology in Colon and Rectal Surgery - Bosio, Raul M.; Pigazzi, Alessio (Clinics in Colon and Rectal Surgery, 2015)
Minimally invasive surgery has changed the way we manage many colon and rectal pathologies. Multiple techniques, from straight laparoscopic procedures, to hand-assisted and single-port techniques are available, requiring surgeons to go through various learning curves. Robotic surgery is a relatively novel technique in general surgery which appears to hold most promise for rectal resection. Laparoscopic rectal procedures are difficult, and even in experienced hands, conversion rates are around 17%. Robotic surgery may be a point of difference in these cases, despite a long learning curve and higher costs. This article will describe the role of robotics in colorectal surgery. Room set up, port placement, and docking strategies will be described for common procedures, with emphasis on a hybrid robotic low anterior resection.
Keywords: robotic colectomy; robotic low anterior resection; robotic colorectal surgery